2017
DOI: 10.1002/2017jd026468
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and greening Tibetan Plateau in early summer in recent decades

Abstract: The Tibetan Plateau (TP) plays an essential role in the global hydrological cycle. Unlike the well‐recognized surface warming, changes in precipitation over the TP and the underlying mechanisms remain ambiguous. A significant increase in the amount of precipitation over the southeastern TP in May over 1979–2014 (13.46% decade−1 of the climatology) is identified in this study, based on homogenized daily rain gauge data. Both the increased precipitation frequency and intensity have contributions. The coherent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 89 publications
(110 reference statements)
11
75
0
Order By: Relevance
“…For the southwestern TP, the greening trend is dominant in winter, spring, and summer (Figures a, b, d–f, and h). The general wetting and greening trend of the TP revealed by our study is consistent with several former studies (e.g., Ding et al, ; Zhang et al, ). Due to the differences in the study periods and NDVI data sources, some discrepancies are observed among these studies.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…For the southwestern TP, the greening trend is dominant in winter, spring, and summer (Figures a, b, d–f, and h). The general wetting and greening trend of the TP revealed by our study is consistent with several former studies (e.g., Ding et al, ; Zhang et al, ). Due to the differences in the study periods and NDVI data sources, some discrepancies are observed among these studies.…”
Section: Resultssupporting
confidence: 93%
“…For example, Ding et al () identified an increase in the NDVI in the southern and eastern TP. Zhang et al () found that the wetting and greening of the TP occurred in early summer. Our study revealed that the wetting and greening trends have heterogeneous characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cold bias can strongly affect future projections of the whole region. In addition, the TP is generally regarded in many studies as a specific high-altitude region that should be separately discussed (Su et al 2013;Zhang et al 2017;You et al 2018). Thus, in this study, we focus on the region of Central Asia, with the TP masked out.…”
Section: Definitions Of Extreme Indices and The Skill Scorementioning
confidence: 99%
“…Therefore, changes in the timing and magnitude of monsoonal rains can have particularly severe impacts on the region's agriculture, surface water and ground water resources (Asoka, Gleeson, Wada, & Mishra, ; Barnett, Adam, & Lettenmaier, ; Gadgil & Gadgil, ; Russo & Lall, ). Changes in the timing of the monsoon can also have non‐local impacts such as over the Tibetan Plateau, where a trend toward early Indian monsoon onset has been associated with enhanced precipitation and greening since the 1970s (W. Zhang, Zhou, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%